Strain energy in human tibia during different exercises with adjustable leg weights: a subject-specific computational model analysis - Guo, Xuan; Xu, XinSheng; Geng, Xiang; Zhang, Zhenming; Ma, Xin; Chen, Wen-Ming (Medical & biological engineering & computing, 2025)
Physical exercise is recommended to improve tibia strength, a common site for stress injuries, while identifying optimal training regimens remains a significant challenge. This study investigated tibial responses to varied exercise regimens using a subject-specific computational modeling approach. A subject-specific neuro-musculoskeletal model was combined with a finite element model to assess the effects of various exercises (jumping, landing, squatting, and walking) on tibial strain energy density (SED), as well as the impact of adjustable leg weights placed at different sites (shank versus thigh). The temporal relationship between joint/muscular loads and SED was then analyzed. A non-linear relationship between load weights and SED increase was observed, with 4% body weight load being the optimal load weight. Additionally, load carriage sites significantly influenced SED levels, emphasizing the necessity for individualized training regimens. The gastrocnemius, soleus, and peroneal muscles were identified as key contributors to tibial SED, with the highest correlations observed during various activities. This study underscored the utility of the subject-specific computational model in assessing the biomechanical impact of varied load weights, load sites, and exercise types. For a target bone site, it is beneficial to customize exercise programs based on individual biomechanical properties in order to maximize training benefits and meanwhile reduce risks of injuries.